Desain Karakter sebagai Alat Advokasi Inklusivitas: Studi Desain Karakter Video Permainan “Concord“ - Alvanov Zpalanzani Mansoor; Ahnaf Setya Erlangga (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2026)
With the rapid growth of the global gaming industry, the practice of conveying progressive values such as DEI (Diversity, Equity, and Inclusivity) through video games has become increasingly widespread. One such example is the emergence of the game “Concord” which has been identified as promoting a wokeness (critical awareness on Issues of social, racial, and discriminatory injustices) towards agenda and has triggered resistance among players. This study aims to examine the role of character design in video games as a medium for advocating inclusive values, focusing on the case study of two characters, IT-Z and Bazz. This research is a qualitative, descriptive, and interpretative study using Roland Barthes’ visual semiotic analysis, which explores the relation between the signifier and the signified about symbolic and mythological meanings within a contemporary social context. The analysis reveals that the character designs in “Concord” represent an explicit effort to present inclusive and racial narratives. However, the reception of this effort is perceived as inorganic, overly artificial, and forced within the context of the video game medium.